Reversal of the CD8+ T-Cell Exhaustion Induced by Chronic HIV-1 Infection Through Combined Blockade of the Adenosine and PD-1 Pathways - Li, Jing; Huang, Hui-Huang; Tu, Bo; Zhou, Ming-Ju; Hu, Wei; Fu, Yu-Long; Li, Xiao-Yu; Yang, Tao; Song, Jin-Wen; Fan, Xing; Jiao, Yan-Mei; Xu, Ruo-Nan; et al. (Frontiers in Immunology, 2021)
Background: Targeting immune checkpoints for HIV treatment potentially provides a double benefit resulting from the ability to restore viral-specific CD8+ T-cell functions and enhance HIV production from reservoir cells. Despite promising pre-clinical data, PD-1 blockade alone in HIV-1-infected patients with advanced cancer has shown limited benefits in controlling HIV, suggesting the need for additional targets beyond PD-1. CD39 and PD-1 are highly co-expressed on CD8+ T cells in HIV-1 infection. However, the characteristics of CD39 and PD-1 dual-positive CD8+ T-cell subsets in chronic HIV-1 infection remain poorly understood. Methods: This study enrolled 51 HIV-1-infected patients, including 40 treatment naïve and 11 ART patients. A total of 11 healthy individuals were included as controls. Different subsets of CD8+ T cells defined by CD39 and/or PD-1 expression were studied by flow cytometry. The relationships between the frequencies of the different subsets and parameters indicating HIV-1 disease progression were analyzed. Functional assays were performed to evaluate the impact of the blockade of adenosine and/or PD-1 signaling on CD8+ T cells. Results: The proportions of PD-1+, CD39+, and PD-1+CD39+ CD8+ T cells were significantly increased in treatment naïve patients but were partially lowered in patients on antiretroviral therapy. In treatment naïve patients, the proportions of PD-1+CD39+ CD8+ T cells were negatively correlated with CD4+ T-cell counts and the CD4/CD8 ratio, and were positively correlated with viral load. CD39+CD8+ T cells expressed high levels of the A2A adenosine receptor and were more sensitive to 2-chloroadenosine-mediated functional inhibition than their CD39- counterparts. In vitro, a combination of blocking CD39/adenosine and PD-1 signaling showed a synergic effect in restoring CD8+ T-cell function, as evidenced by enhanced abilities to secrete functional cytokines and to kill autologous reservoir cells. Conclusion: In patients with chronic HIV-1 infection there are increased frequencies of PD-1+, CD39+, and PD-1+CD39+ CD8+ T cells. In treatment naïve patients, the frequencies of PD-1+CD39+ CD8+ T cells are negatively correlated with CD4+ T-cell counts and the CD4/CD8 ratio and positively correlated with viral load. Combined blockade of CD39/adenosine and PD-1 signaling in vitro may exert a synergistic effect in restoring CD8+ T-cell function in HIV-1-infected patients .